Pengaruh Loneliness terhadap Internet Gaming Disorder dengan Self-Control sebagai Moderator - Varadina Azaliaputri; Lilim Halimah (UNISBA Press, 2022)
Abstract. Online game is at the forefront of the entertainment industry. The increasing number of downloads and use of online games lead individuals to be highly involved and it is at risk of being internet gaming disorder. Internet gaming disorder is prone to be experienced during the developmental stage of emerging adulthood in order to overcome psychological problems, such as loneliness. However, it is found the diverse relationship between loneliness and internet gaming disorder. Self control is predicted as a variable that can act as a moderator of both variables. This study aims to find out how strong the influence of loneliness on internet gaming disorder with self-control as a moderator variable. This study used Quantitative method. The participants in this study are 97 emerging adults in Bandung Raya, who were selected using purposive sampling technique. Instruments that are used in this study are Internet Gaming Disorder Scale, UCLA Loneliness Scale Version 3, and Brief Self-Control Scale. The result shows that the regression coefficient between loneliness and internet gaming disorder P = .050 ≤ 0.05. It means that loneliness does not influnce on internet gaming disorder and self-control does not moderate the relationship of the two variables. Abstrak. Bermain game online berada di barisan depan industri hiburan. Meningkatnya jumlah pengunduhan dan penggunaan game online mengarahkan individu kepada keterlibatan tinggi dengan game online sehingga dapat berisiko mengalami internet gaming disorder. Internet gaming disorder rentan dialami individu pada masa perkembangan emerging adulthood untuk mengatasi permasalahan psikologis, seperti loneliness. Namun demikian, terdapat temuan yang beragam tentang hubungan antara kedua variabel tersebut. Kontrol diri merupakan variabel yang diprediksi berperan memoderatori kedua variabel tersebut. Penelitian ini bertujuan untuk mengetahui seberapa kuat pengaruh loneliness terhadap internet gaming disorder dengan self-control sebagai moderator. Sampel dalam penelitian ini berjumlah 97 emerging adults di Bandung Raya dengan teknik purposive sampling. Digunakan alat ukur Internet Gaming Disorder Scale, UCLA Loneliness Scale Version 3, dan Brief Self-Control Scale. Hasil uji statistik menunjukkan nilai koefisien regresi antara loneliness terhadap internet gaming disorder sebesar P = .050 ≤ 0.05. Sehingga dapat disimpulkan bahwa loneliness tidak signifikan dalam mempengaruhi internet gaming disorder dan self-control tidak berperan sebagai variabel moderator bagi hubungan kedua variabel tersebut.